2013
DOI: 10.1155/2013/354017
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Occlusal Force Distribution and the Activity of Masseter and Anterior Temporalis Muscles in Asymptomatic Young Adults

Abstract: Healthy subjects have a prevalent side on which they display higher-muscle activity during clenching. The relationship between symmetry of masseter muscle (MM) and anterior temporalis (TA) muscle activities and occlusion has been evaluated on the basis of physiological parameters. The aim of the present study was to investigate whether the symmetry of surface EMG (sEMG) activity in asymptomatic young adults is related to symmetry of occlusal contacts. Material. The study population consisted of seventy-two 18-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 19 publications
2
36
0
Order By: Relevance
“…Additional technical facts are as follows: differential gain = 5,000; input impedance = 10 11 Ohms; noise ≤ 0·3 microvolt average; common mode rejection ratio ≥ 130 dB; the resolution of the 16‐bit Analog to Digital converter = 0·0305 microvolts. For further information about the machine, please refer to .…”
Section: Methodsmentioning
confidence: 99%
“…Additional technical facts are as follows: differential gain = 5,000; input impedance = 10 11 Ohms; noise ≤ 0·3 microvolt average; common mode rejection ratio ≥ 130 dB; the resolution of the 16‐bit Analog to Digital converter = 0·0305 microvolts. For further information about the machine, please refer to .…”
Section: Methodsmentioning
confidence: 99%
“…According to the manufacturer, it is an ideal complement to articulating paper, identifying premature contacts and interferences in the occlusion dynamics. Various studies have evaluated the performance of the several generations of T‐Scan ® that exist (, while others have applied it as a reference instrument . The T‐Scan ® system measures relative force, that is, in arbitrary units corresponding to the internal digital (or ‘raw’) level.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the symmetry of surface electromyography activity is not related to symmetry of occlusal contacts [5], so during chewing some zones can be subjected to higher interarch occlusal forces than others. Therefore, orthodontic appliances often have to withstand variable masticatory loads, thus causing unwanted appliances debonding [6].…”
Section: Introductionmentioning
confidence: 99%